BAHAYA ROKOK TERHADAP KONSUMSI ROKOK DI BANDA ACEH - Puput Arisna; Eddy Gunawan (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2016)
This study aimed to analyze the effect of tobacco customs rates and dangers picture message of smoking on cigarette consumption. However, this study also analyzes other factors such as local government policies such as smoking area as well as to analyze the influence of income and expenditure on cigarette consumption. The data used in this research is data result of observation, interviews, questionnaires and literature study. Samples in this study were 50 smokers using large sample. The model used is the Multiple Linear Regression (Ordinary Least Square). The results showed that the tobacco tax, smoking area, and spending on cigarettes positive and significant impact on the level of cigarette consumption. While the dangers of smoking message display and the level of income and own a significant negative impact on the level of cigarette consumption. Central and local government is expected to establish appropriate policies that can reduce the level of society tobacco consumption.